Mengukur Kelayakan Angka Kemiskinan Kabupaten/Kota di Provinsi Bengkulu Periode Maret 2020 - Fatmasari Damayanti (UNIB Press, 2022)
Survey quality is affected by two types of errors, namely non-sampling errors and sampling-related errors. One measure commonly used to measure the accuracy of the parameters is standard error (SE). If SE is divided by the statistical value and expressed as a percent, the Relative Standard Error (RSE) is obtained. In addition, another measure used to measure the quality of survey results is the design effect (DEFF). The Poverty Rate is one of the figures generated from the National Economic Survey. This study aims to calculate the RSE and DEFF of the Regency/City Poverty Rates in Bengkulu Province for the March 2021 period using the R software. This means that the quality of the estimation results of the City district poverty rate in Bengkulu Province for the March 2020 period is accurate and feasible to use. However, the resulting DEFF value is more than 1, which means that the survey design used is less efficient because it produces a higher SE value than if using a simple random sampling design.